Evaluation of the effectiveness of occlusal splint therapy and exercise therapy on temporomandibular disorders: A systematic review - Cahyani, Irvi; Chairunnisa, Ricca; Norasmatul Akma, Ahmad (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Temporomandibular disorders (TMD) involve the temporomandibular joint, masticatory muscles, and associated structures, presenting with various symptoms such as difficulty in chewing, speaking, and other orofacial functions. Common treatment options for TMD include occlusal splint therapy and exercise therapy. This study aims to evaluate the effectiveness of occlusal splint therapy and exercise therapy in managing TMD through a systematic review. Methods: Literature searches were conducted in PubMed, ProQuest, and Google Scholar, covering publications from 2012 to 2022. The keywords used included (